CULTURAL HERITAGE AS THE BASE FOR THE DEVELOPMENT OF EDUCATIONAL TOURISM IN BIAUNG VILLAGE, PENEBEL, TABANAN - Putu Widya Darmayanti; I Made Darma Oka; Ketut Sumadi (UHN IGB Sugriwa Denpasar, 2022)
Biaung Village has some potential to develop into a cultural tourism attraction. This article aims to examine the existence of cultural heritage in this village to be developed into educational tourism. The data was collected by observation, literature study, and in-depth interviews with local community leaders and then analyzed by descriptive qualitatively. The results showed that the cultural heritage of Biaung Village is feasible to be developed into educational tourism for tourists, especially the younger generation. Hence, the younger generation has a strong understanding of cultural preservation in the future. It can be seen in the offer of educational tour packages (relics of ancient cultural sites, Batur Sari Murti Temple, tradition of making